Fissidens brachypus : A moss restricted to a freshwater Amazonian sponge - Buck, William R.; Pursell, Ronald A. (Amazoniana, 1980)
The presence of the moss Fissidens brachypus Mitt. is reported for the first time in BraziL This mss occurs only on a fresh water sponge, Metanh redcubta (Bowerbank). The relation between the two organisms represents an ecology different than that of other sponge associations. FissYiens brachypus is compared with F. stissothem and F. substissothem.
Keywords: Musgo Fissidens Brachypus Mitt